Effects of Acute Physical Exercise With Low and High Cognitive Demands on Executive Functions in Children: A Systematic Review - Paschen, Linda; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : Whereas many studies addressed the relation between acute physical exercise and executive functions (EF) in children, the effects of various modalities of acute exercise on EF still remain unclear. This systematic review investigated the effects of exercise with low and high cognitive demands on speed of processing and accuracy of performance in tasks examining inhibition, working memory, and cognitive flexibility in children. Method : A systematic literature research in electronic databases was performed. Controlled trials assessing the effects of acute exercise on EF in a pre–post design were included. Results : Ten studies involving a total of 890 participants revealed positive effects in working memory performance in speed of processing after acute exercises with low cognitive demands compared with seated rest, mixed results for inhibition after exercises with low and high cognitive demands, and mixed results for cognitive flexibility with low cognitive demands. Concerning accuracy, only mixed results were found for inhibition after exercises with low and high cognitive demands. Conclusion : The differentiated effects of acute exercises with low and high cognitive demands led to more positive effects in speed of processing compared with accuracy of performance. Further investigations including assessment of neurophysiological parameters of EF are needed.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health